PENGARUH CORPORATE GOVERNANCE TERHADAP LUAS PENGUNGKAPAN SUKARELA (STUDI EMPIRIS PADA PERUSAHAAN PERBANKAN YANG LISTING DI BEI TAHUN 2009-2012) - Silaban, Yudika Amanda; -, Kennedy; Ali, Al Azhar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this research to test the effect of Institution ownership, Managerial ownership, independent board size, and audit comitee to quality of voluntary disclosure in the Financial Statement on Banking company in the Indonesia Stock Exchange during the year 2009 -2012. The population on this research is Banking firms listed on the Indonesia Stock Exchange during the year 2009 – 2012. Based on purposive sampling method acquaired 31company as the sample in this research. The test carried out by the method of multiple regression, the processing of data SPSS for windows version 20. The result of this research indicate that the independent board size were not significant and not effected to the quality yof volountary dislousure on the financial statement, while the institution ownership, managerial ownership, and audit comitee have significant effect on the quality of volountary dislousure of financial statements. Based on the test result the coefficient of determination, the value of adjust R square of 14.3 % while the remaining 85.7 % is influenced by other variables aren’t include on this research.Keywords: Financial Statement, volountary disclosure, Institution ownership, Managerial ownership,indepdndent board size, audit comite